Empire of the people : settler colonialism and the foundations of modern democratic thought - Dahl, Adam (American political thought., 2018)
"Adam Dahl examines the ideological development of American democratic thought in the context of settler colonialism, a distinct form of colonialism aimed at the appropriation of Native land rather than the exploitation of Native labor. By placing the development of American political thought and culture in the context of nineteenth-century settler expansion, his work reveals how practices and ideologies of Indigenous dispossession have laid the cultural and social foundations of American democracy, and in doing so profoundly shaped key concepts in modern democratic theory such as consent, social equality, popular sovereignty, and federalism. To uphold its legitimacy, Dahl also argues, settler political thought must disavow the origins of democracy in colonial dispossession--and in turn erase the political and historical presence of native peoples. Empire of the People traces this thread through the conceptual and theoretical architecture of American democratic politics--in the works of thinkers such as Thomas Jefferson, Thomas Paine, Alexis de Tocqueville, John O'Sullivan, Ralph Waldo Emerson, Daniel Webster, Abraham Lincoln, Walt Whitman, and William Apess. In its focus on the disavowal of Native dispossession in democratic thought, the book provides a new perspective on the problematic relationship between race and democracy--and a different and more nuanced interpretation of the role of settler colonialism in the foundations of democratic culture and society."--Publisher's web-site.